(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
During his 35-year rule, the master Amir Temur was ready to fight against the powerful rulers of his time for the peace and tranquility of his country. Timur did not stop his enemies during military campaigns and this played a big role in his victories. Many historians include Alexander the Great and Amir Temur among the three great generals and Genghis Khans, and among them, they highly value Temur’s work. This is a correct opinion, because neither Alexander nor Genghis Khan found a worthy opponent in their time. Amir Temur’s opponents were rulers who threatened the whole of Europe and Russia in their time. There were times when Temur was defeated in his time, but he always regained his strength for the peace of his country.